Small (<4 cm) renal mass: differentiation of angiomyolipoma without visible fat from renal cell carcinoma utilizing MR imaging - Sasiwimonphan, Kewalee; Takahashi, Naoki; Leibovich, Bradley C; Carter, Rickey E; Atwell, Thomas D; Kawashima, Akira (Radiology, 2012)
To determine whether a combination of magnetic resonance (MR) parameters can help differentiate small angiomyolipomas (AMLs) without visible fat from renal cell carcinomas (RCCs). This HIPAA-compliant retrospective study received institutional review board approval; 69 men and 42 women (mean age, 59.7 years) with 15 AMLs without visible fat and 104 RCCs underwent MR. The development set consisted of 10 AMLs and 71 RCCs; the validation set consisted of five AMLs and 33 RCCs. T1-weighted fast spin-echo (SE), fat-suppressed T2-weighted fast SE, in- and opposed-phase gradient-echo (GRE), and fat-suppressed three-dimensional T1-weighted spoiled GRE sequences were performed before and after contrast material administration. Tumor signal intensity (SI) was measured. T1 and T2 SI ratio (ratio of tumor to renal cortex SI on T1- and T2-weighted images, respectively), SI index (SII) ([SI(in) 2 SI(opp)]/[SI(in)] × 100; SI(in) and SI(opp) are tumor SI on in- and opposed-phase images, respectively), and arterial-to-delayed enhancement ratio ([SI(art) 2 SI(pre)]/[SI(del) 2 SI(pre)]; SI(pre), SI(art), and SI(del) are tumor SI on unenhanced, arterial phase, and delayed phase three-dimensional T1-weighted spoiled GRE images, respectively) were compared. Combinations of MR parameter threshold levels were constructed from development set and validated with validation set. Sensitivity, specificity, and accuracy for differentiating between AML and RCC were calculated for combinations of MR parameter threshold levels. AML had significantly higher T1 SI ratio (P = .04), lower T2 SI ratio (P = .001), higher SII (P = .02), and higher arterial-to-delayed enhancement ratio (P < .001) than RCC. Sensitivity, specificity, and accuracy for combination of T2 SI ratio less than 0.9 and ([SII greater than 20% and T1 SI ratio greater than 1.2] or arterial-to-delayed enhancement ratio greater than 1.5) were 73% (11 of 15), 99% (103 of 104), and 96% (114 of 119), respectively, for differentiating AML from RCC. A combination of T2 SI ratio less than 0.9 and ([SII greater than 20% and T1 SI ratio greater than 1.2] or arterial-to-delayed enhancement ratio greater than 1.5) was accurate in differentiating AML from RCC.